Hip fracture treatment and complications after surgery - Garcia Santiago, Gerardo; Torres Magaña, Esteban; Ponce Galvez , Ana Sofia; Alejandro Rodriguez Ceja , Aran; Avalos Gonzalez, Guillermo (International Journal of Advances in Medicine, 2023)
Falls are one of the most important geriatric syndromes due to their high frequency, often without fatal consequences, but they do tend to affect the person’s health and quality of life. The purpose of this review is to mention to most used options of treatment and the most common complication that occurred after the treatment. Whether physical or psychological complications. The average age is 82 years in women and 79 years in men; the largest number of causes occur during the day and at home, which is why more than 40% of the population has suffered a previous fracture. Most fractures are the result of trips or falls, but there are 5% who do not report previous traumatic episodes. The most common types of fracture according to the AO/OTA classification correspond to type 31-A1 and 31-A2 which are considered stable, likewise it is mentioned that the scope of treatment commonly used is intramedullary nailing and sliding screw plate, being the second one the preferred one. The risk factors associated with this complication were age, sex, and ASA score. In another way, the surgical complications included hematoma/healing, mechanical disorder, complications, infections, Necrosis, pseudoarthrosis, and malposition Healing and had the same risk factors associated plus the time it took to perform the surgery.